1989
DOI: 10.1073/pnas.86.18.7027
|View full text |Cite
|
Sign up to set email alerts
|

Assay of vacuolar pH in yeast and identification of acidification-defective mutants.

Abstract: As part of a genetic analysis of the biogenesis and function of the vacuole (lysosome) in the yeast Saccharomyces cerevisiae, assays of vacuolar pH were developed and used to identify mutants defective in vacuolar acidification.Vacuoles were labeled with 6-carboxyfluorescein with the membrane-permeant precursor 6-carboxyfluorescein diacetate. Dual-excitation flow cytometry was used to calibrate the pH-dependence of 6-carboxyfluorescein fluorescence in vivo.Vacuoles in wild-type yeast were mildly acidic, pH 6.2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
118
0

Year Published

1996
1996
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(130 citation statements)
references
References 33 publications
12
118
0
Order By: Relevance
“…3A). Microscopic observation of vacuolar acidification with quinacrine fluorescence [26] showed a complete inhibition of vacuolar acidification of S. pombe cells by 10 lM concanamycin A (data not shown), suggesting no active transport of 2-DG into vacuoles.…”
Section: Involvement Of Vacuolar Compartmentalization In Amino Acidmentioning
confidence: 92%
“…3A). Microscopic observation of vacuolar acidification with quinacrine fluorescence [26] showed a complete inhibition of vacuolar acidification of S. pombe cells by 10 lM concanamycin A (data not shown), suggesting no active transport of 2-DG into vacuoles.…”
Section: Involvement Of Vacuolar Compartmentalization In Amino Acidmentioning
confidence: 92%
“…V-ATPase subunit genes have fication by V-ATPases is important for receptor-ligand been identified through a variety of biochemical apuncoupling in the biosynthetic and endocytic pathways, proaches (Nelson et al 1989(Nelson et al , 1994 Beltran et zymogen activation, and cellular pH homeostasis. Supekova et al 1995) and genetic screens pH gradient generated by the V-ATPases can energize (Preston et al 1989;Ohya et al 1991;Ho et al 1993). uptake of Ca 2ϩ , amino acids, and other ions and metaboAlthough loss of V-ATPase activity in higher eukarylites (Nelson and Harvey 1999;Nishi and Forgac otes is lethal, disruption of any of the VMA genes in 2002).…”
Section: Acuolar Proton-translocating Atpases (V-atp-mentioning
confidence: 99%
“…The yeast V-ATPase has emerged mentable carbon sources, or in the presence of a variety as the predominant model system for eukaryotic V-ATPof heavy metals. Vph1p was identified through a screen ases because it closely resembles the enzyme in higher for vacuolar acidification defects (Preston et al 1989; eukaryotes but is more easily manipulated genetically Manolson et al 1992). Deletion of VPH1, which enand biochemically (Nelson and Klionsky 1996; Kane codes the vacuole-specific a-subunit isoform, results in and Smardon 2003).…”
Section: Acuolar Proton-translocating Atpases (V-atp-mentioning
confidence: 99%
“…Inactivation of any of the genes encoding V-ATPase subunits so far identified in S. cere isiae, with the exception of Vph1p, leads to loss of V-ATPase function. The resulting phenotype is not lethal, but there is a failure to grow in medium buffered to pH 7.5, sensitivity to high extracellular calcium concentrations and a dysfunctional vacuole [54][55][56][57][58][59][60][61] Other genes giving rise to the same phenotype [62] are present that encode polypeptides not yet identified as components of the V-ATPase, but which could possibly be involved in assembly, targeting or regulation of the enzyme. In addition, genes have been found that encode polypeptides with sequence similarity to identified V-ATPase subunits but whose function is not yet clear (see section 5.2.…”
Section: Genetic Analysis Of V-atpase Subunitsmentioning
confidence: 99%
“…An equivalent, if somewhat smaller, polypeptide is encoded by the I-gene in the Ntp gene cluster of Enterococcus [53]. A corresponding yeast 96 kDa protein was cloned by complementation of the ph1 mutation [54] and found to have 42 % identity with the rat protein [147], and all 116 kDa-related proteins sequenced to date appear to share a bipartite structure, with extensive N-terminal hydrophilic domain and a C-terminal domain containing up to seven putative membrane-spanning hydrophobic segments. The membrane topology of the protein remains unclear, but its sensitivity to proteolysis has led to the suggestion that the Nterminal domain is cytoplasmically exposed.…”
Section: -116 Kda Subunitmentioning
confidence: 99%